Medical postcard from Australia, the world's largest island. (1st June 2013) - Coleman, Justin; Hesp, Blair
Abstract : The Australasian Medical Writers Association (AMWA) comprises about 300 journalists, writers, editors, and health professionals based in Australia and nearby island nations, particularly New Zealand and Fiji. AMWA has held a popular conference annually since its formation in 1982. Members whose writing is essentially product promotion are restricted to affiliate membership, and AMWA does not accept sponsorship from the pharmaceutical industry.